Study of Serum Creatinine in Female Type 2 Diabetes Mellitus Patients - Hussain, Maria; Naznin, Rubaiyat; Naznen, Farhana (Community Based Medical Journal, 2024)
Diabetes mellitus is a chronic illness that affects millions of individuals worldwide. In the present study serum creatinine was estimated in female type 2 diabetes to observe the frequency of increase serum creatinine level in these patients. A cross-sectional, descriptive study was carried out in the Department of Physiology, Mymensingh Medical College, Bangladesh, between July 2016 and June 2017. A total of 210 subjects were selected and were grouped as: control group (group I) having 70 healthy female of reproductive age (21-45 years) and study group (group II), which was again subdivided to group IIA (70 diabetic female of reproductive age (21-45 years) and group IIB (70 diabetic female of post-menopausal age, 45-70 years). Laboratory analysis of serum creatinine was done by enzymatic colorimetric method. A comparison in serum creatinine concentration was done in between group I and group II and in between Group IIA and Group IIB. The results were calculated and analyzed by using SPSS. For statistical analysis students unpaired ‘t’ test was performed. Our study revealed that serum creatinine was increased among females of the study group and the result was statistically significant. In the control group serum creatinine was within the normal physiological range. CBMJ 2024 July: vol. 13 no. 02 P: 198-202